2017
DOI: 10.1042/bsr20170243
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy and safety between dezocine injection and morphine injection for persistence of pain in Chinese cancer patients: a meta-analysis

Abstract: The association between the efficacy and safety of dezocine injection and morphine injection for persistence of pain in patients with cancer had yielded controversial results. Therefore, we conduct a meta-analysis of existing observational published studies to assess the relationship between them among Chinese. We conducted a comprehensive research from the databases of PubMed, Web of Science, and Wan Fang Med Online for the related studies up to October 2016. Summary odds ratio (OR) with 95% confidence interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 16 publications
(14 reference statements)
0
22
0
Order By: Relevance
“…Studies have shown that radiotherapy and chemotherapy can increase the risk of myelodysplastic disorder and acute myeloid leukemia in BC patients, which means more pain for patients with poor body function and poor tolerability [2]. Traditional Chinese medicine (TCM), as a traditional medicine for adjuvant treatment of tumors, has the effect of improving the immune function and tumor microenvironment of the patients and reducing the toxicity of radiotherapy and chemotherapy, so as to improve the survival rate [3][4][5][6][7]. It is shown that compound Kushen injection (CKI), as a TCM compound preparation, has a good synergistic antitumor effect by inhibiting tumor cell proliferation and inducing differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that radiotherapy and chemotherapy can increase the risk of myelodysplastic disorder and acute myeloid leukemia in BC patients, which means more pain for patients with poor body function and poor tolerability [2]. Traditional Chinese medicine (TCM), as a traditional medicine for adjuvant treatment of tumors, has the effect of improving the immune function and tumor microenvironment of the patients and reducing the toxicity of radiotherapy and chemotherapy, so as to improve the survival rate [3][4][5][6][7]. It is shown that compound Kushen injection (CKI), as a TCM compound preparation, has a good synergistic antitumor effect by inhibiting tumor cell proliferation and inducing differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, one meta-analysis reported that there is no significant difference between dezocine and morphine injections on the persistence of pain in patients with cancer among Chinese patients. 22 A pilot study by Zhu et al 13 showed that the analgesic efficacy of dezocine was similar to that of sufentanil. Dezocine combined with sufentanil can provide effective postoperative analgesia for PCIA in burn patients after escharectomy or tangential excision followed by autologous skin grafting.…”
Section: Discussionmentioning
confidence: 99%
“…35 Our findings demonstrate that the incidence of lethargy and PONV in Group D was significantly lower than the incidence in Group S. This difference was statistically significant ( P <0.05), suggesting that dezocine might be an antagonist of the μ receptor, without μ receptor agonist side effect, capable of relaxing the gastrointestinal smooth muscle and reducing the incidence of PONV. 36 Wang et al 22 revealed that the rate of adverse drug reactions caused by dezocine injection was 56% lower than that caused by morphine injection. A study by Bian et al 38 revealed that morphine and sufentanil may dose-dependently increase the contractile tension and contraction ability of isolated rat small intestine smooth muscle, but dezocine had no significant effect on intestinal smooth muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sevo urane has been revealed to function as an anti-tumor reagent in different types of cancer, including ovarian cancer [12][13][14]. As a representative opioid-receptor agonist/antagonist, dezocine has been widely used in clinical anesthesia and analgesics for postoperative cancer with minimal side effects [15][16][17]. Feng C et al previously report that dezocine could regulate the secretion of IL-12 and IL-10 in dendritic cells and enhance the activity of T cells during the maturation of dendritic cells, affecting immune function [18].…”
Section: Introductionmentioning
confidence: 99%